PERAN AI DALAM PENGEMBANGAN METODE PEMBELAJARAN PENERJEMAHAN BAHASA ARAB DI ERA DIGITAL - Rafly Fighter Mahda; Zulhannan; Ahmad Iqbal; Intan Muflihah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The rapid development of digital technology has significantly transformed language learning, including Arabic translation studies at the university level. This research aims to investigate the role of Artificial Intelligence (AI) in enhancing translation learning methods among seventh-semester students who actively utilize AI-based applications such as Google Translate, ChatGPT, Cici AI, Claude AI, and DeepSeek AI. Using a qualitative descriptive approach, data were collected through in-depth interviews, participatory observation, and documentation, involving three purposively selected informants. The findings reveal that AI assists students in understanding sentence structures, analyzing contextual meanings, and verifying translation results across multiple platforms. AI also improves learning efficiency and supports independent learning by providing alternative lexical choices and detailed explanations. However, limitations such as semantic bias, inaccuracies in idiomatic texts, and risks of overreliance on technology remain challenges. This study concludes that AI plays a strategic role in translation learning and is highly relevant for developing more interactive, analytical, and autonomous learning models. The implications highlight the need for guided pedagogical integration, further comparative research across AI platforms, and institutional support in digital literacy strengthening.